2015
DOI: 10.1111/ppa.12454
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the viable but nonculturable state in Clavibacter michiganensis subsp. michiganensis and in planta resuscitation of the cells on tomato seedlings

Abstract: Bacterial canker of tomato is an economically important seedborne disease caused by Clavibacter michiganensis subsp. michiganensis (Cmm). Copper‐based bactericides and seed treatment with hydrochloric acid are commonly used for bacterial canker management. Recent studies have shown that some bacteria can enter a viable but nonculturable (VBNC) state, and fail to form colonies on microbiological agar media. Bacteria in the VBNC state can recover their culturability when returned to favourable conditions. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
(66 reference statements)
0
35
0
4
Order By: Relevance
“…of the seed microbiota may be inactive or dormant [65,66], it seems unlikely that priority effects play a major role in a seed ultimate community structure, though this remains to be tested specifically. Still, we can hypothesize the general drivers that may be niche or neutral in seed microbiota assembly.…”
Section: Current Opinion In Microbiologymentioning
confidence: 94%
“…of the seed microbiota may be inactive or dormant [65,66], it seems unlikely that priority effects play a major role in a seed ultimate community structure, though this remains to be tested specifically. Still, we can hypothesize the general drivers that may be niche or neutral in seed microbiota assembly.…”
Section: Current Opinion In Microbiologymentioning
confidence: 94%
“…The challenge in detecting Cmm is that the bacterium enters a viable but nonculturable (VBNC) state under stress conditions [ 14 ]. VBNC is defined as metabolically active but without the ability to grow on conventional media [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LIVE/DEAD Bac Light Bacterial Viability Kit has been widely used to distinguish live cells [ 16 , 20 ]. Jiang et al used this chemical treating bacteria prior to measuring the Cmm population with the flow cytometry method to count viable Cmm cells, combined with agar plating assay to enumerate VBNC cells [ 14 ]. However, this method cannot be used to detect the VBNC Cmm cells from a real sample, such as seed extract, because the flow cytometry method cannot differentiate between Cmm and other bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial cells can be recovered or resuscitated from harsh stress by suitable environmental conditions, allowing the resuscitated cells become culturable. It has been reported that Cm could be induced into VBNC state under stress conditions of low pH and Cu 2+ , and then resuscitated by addition of nutrient or inoculation in planta (Jiang et al 2016). It is well known that ppGpp can accumulate and act as an alarmone molecule in the regulation of growth and survival in bacteria when adverse conditions are encountered.…”
Section: Introductionmentioning
confidence: 99%